MODULAR BAMBOO STRUCTURE DESIGN EXPLORATION WITH DEPLOYABLE CONSTRUCTION SYSTEM - Dwiana (Jurnal Riset Arsitektur, 2019)
Abstract- Deployable structure is a type of structure that can be transformed from a closed configuration to an open configuration. This structure can be assembled and disassembled with ease. This easy construction is a reason why deployable structure is the right structure for after disaster scenario. In emergency, natural resources are needed since it can be found and used easily. Bamboo is a common plant that can be found everywhere in Indonesia.  Research have been done by UNPAR’s architecture lecturer regarding deployable structure (deployable spatial and deployable planar) with bamboo as its material. It says that deployable spatial structure has easier and shorter time in instalation than deployable planar structure. Deployable spatial structure has tons of room for development. Some development that can be done is to make deployable structure module to be duplicated in every direction, and to implement self locking mechanism in this structure. This research is done to find deployable structure module that can be duplicated in every direction, and also implementing self locking mechanism in this structure Method that used in this research is qualitative by comparing some buildings that implementing deployable system (Resiploy and Triangle Prism) and modular system (Rising Canes and Y-BIO). The comparastion result is opportunity and thread from each building. This result which is opportunity and thread from each building then synthesized to find criteria for deployable structure that can be duplicated in every direction. Based on the research, it can be concluded that in deployable structure, nut and bolt is needed so that some building element can be rotated to create a movement. In modular building, we need a simple system that can be used in every joint so that building can be duplicated in every way with ease. Reciprocal structure is needed to make a building with self locking mechanism. By simplifying Resiploy’s joint and using Rising Canes’s modules, we can make a deployable structure that can be duplicated in every way with self locking mechanism  Key Words: bamboo structure, deployable, modular, self locking mechanism